Theatrum in older Czech literature. Reflecting the concept by Eduard Petrů - Bočková, Hana (Bohemica Olomucensia, 2019)
This study sums up the methodology of literary work by Eduard Petrů in the field of early modern literature. It reflects his account of "theatrum" as a term, including its use in respective literature. First, its genesis since antiquity and early Christian beginnings is covered, together with the term's semantic scope modification during the Renaissance. Reflecting the spread of analogic thinking, the study traces Petrů's concept of genre constitution based on "theatrical metaphor" which enables the depicted reality to be approached universally, be it the world as a whole or any of its parts. The author of the study ponders on Petrů's characteristics of moralist texts based on semantics of "theatrum microcosmi" (i.e. Theatrum mundi minoris by Nathanael Vodňanský of Uračov) and encyclopaedic writings based on semantics of "theatrum macrocosmi" (i.e. Theatrum divinum by Matouš Konečný, the plan of Theatrum universitatis rerum by Jan Amos Komenský).
Keywords: theatrical metaphor; theatrum microcosmi; theatrum macrocosmi; Theatrum mundi minoris by Nathanael Vodňanský of Uračov; Theatrum divinum by Matouš Konečný; Theatrum universitatis rerum by Jan Amos Komenský